Role of compliant porosity in stress dependency of ultrasonic velocities in carbonates and sandstones - De Paula, Osni; Pervukhina, M.; Gurevich, Boris (SBGf, 2008)
A study of complex dual-nature porosity of reservoir rocks is necessary for quantitative understanding of seismic wave propagation in reservoirs. We analyze here the ratios of stiff and compliant porosities in 6 samples of carbonates and 6 samples of sandstones, and effect of compliant porosity on ultrasonic shear and compressional wave velocities measured at effective stresses from 0 to 60 MPa. The compliant porosity is estimated from stress dependency of dry rock compressibility using isotropic Shapiro theory (2003). In the case of sandstones, we have direct measurements of porosity variations with pressure whichvalidate the estimated compliant porosities. Finally, we use Gassmann equations to estimate the stress dependence of shear and compressional wave velocitiesin saturated rocks. Two examples discussed here show that a better estimation is obtained using the high frequency unrelaxed frame shear and bulk modulus(Mavko&Jizzba,1991) to “saturate” the samples.